Исследование жирнокислотного состава соцветий Tagetes erecta L. var. «Alaska» - Малюгина, Е. А.; Смойловская, Г. П.; Мазулин, А. В.; Maliuhina, O. O.; Smoilovska, H. P.; Mazulin, O. V.; Малюгіна, Олена Олександрівна; Смойловська, Галина Павлівна; Мазулін, Олександр Владиленович (SWorld &D.A. TsenovAcademy of Economics - Svishtov,Bulgaria, 2020)
В работе рассматриваются результаты определения содержания жирных кислот в соцветиях бархатцев прямостоячих сорта «Аляска». Изучение качественного состава и количественного соотношения жирных кислот в растительном сырье изучали методом газовой хроматографии. В составе соцветий Tagetes erecta L. var. «Alaska» определено 9 жирных кислот, среди которых преобладают ненасыщенные жирные кислоты (до 75,46±3,77 %), преимущественно линолевая, олеиновая и линоленовая. Насыщенных жирных кислот (в количественном отношении) существенно меньше, среди них преобладают стеариновая и пальмитиновая. Abstract. Marigolds (Tagetes erecta L.) is one of the most common and widely cultivated species of the genus Tagetes L. of family Asteraceae. Plants of the genus Tagetes L. are known for a wide range of biological activity and the content of various classes of biologically active substances. Marigold contains more than 100 biologically active substances: carotenoids, flavonoids, hydroxycinnamic acids, essential oils, vitamins, and fatty acids. Fatty acids in the human body perform a number of important functions. They participate in the synthesis of prostaglandins and thromboxanes, the formation of biological membranes, and the metabolism of vitamins. So fatty acids are promising for obtaining a wide range of medicine. There is almost no information about the fatty acid profile of Tagetes erecta L. in the literature. Therefore, the study of the content of fatty acids in the plant raw materials of Tagetes erecta L. is important scientific and practical value. The aim of this work is to study the fatty acid composition of Tagetes erecta L. var. "Alaska".
Study of the fatty acids’ composition of inflorescences of Tagetes erecta L. var. «Alaska»
Keywords: бархатцы; Tagetes erecta L.; жирные кислоты; marigolds; fatty acids